Virtual Focus Group Discussions: the new normal way to promote reflective practice. Issue 2 (4th March 2022) - Pineda, Josephine Luz de Leon; Villanueva, Rose Lynn de Dios; Tolentino, Joyce Ann Macatuno
ABSTRACT: Academic institutions were not spared from the onslaught of the global pandemic as they were forced implement radical changes in academic policies. Adapting to the new normal way of learning, teacher education institutions should provide experiences and opportunities among student teachers (STs) to become reflective practitioners. Virtual Focus Group Discussions (VFGDs) offer a venue for STs to discuss their practicum experiences with their peers and teachers in the new normal set-up. This study aimed to find out how STs described their experiences in conducting VFGD for reflective practice; and to uncover their perceptions in the use of VFGD as a means to promote reflective practice and as part of teacher training. Qualitative action research design was utilized, following the plan-do-study-act (PDSA) cycle that will help teachers improve their practice. Graduating elementary educators were the participants. The findings discussed the reflective practice of the participants and the conduct of the intervention. This provides teacher educators and future researchers with a guide in conducting the same or similar experiences among STs undergoing their practicum.